STUDENTS’ PERSPECTIVE ON USING TRANSTOOL IN CONVERTING ENGLISH TEXT TO INDONESIAN - Yovita Angelina; Magpika Handayani (STKIP Persada Khatulistiwa Sintang, 2020)
This study aims at analyzing the usage of the Translate Tool in converting English text at Sekolah Tinggi Bahasa Asing Students. The analysis is based on Translation Tools that commonly used by students to help in learning. Sekolah Tinggi Bahasa Asing is one of the colleges in Pontianak and one of the subjects that is taught in translation. The method in this research is descriptive qualitative research. The writer took 15 students of Sekolah Tinggi Bahasa Asing as a participant. These 15 students having a high score in translation subjects and frequently using the Translation Tool for writing or speaking in class. The result of the interview tells that the use of a translation tool in converting text from a book and help them understand instruction that is given by the lecturer. Translation tool helps students to understand the instruction easily and make their work quicker compared to manual process. The feature of translation tool is easy to use that make this application is easily operated; moreover, The students are not only helped to convert for their field of study, but the application also can be used to help students converting another field of study that is not learnt by them.